Credentialing (in laser surgery) - Wright, V. Cecil; Riopelle, Mary Ann (Operating Room Nurses Association of Canada Journal, 1990)
The success of a laser program, like that of any multidisciplinary project, depends on co-operation among many individuals and institutional departments. Consistent monitoring of the function of the entire laser program, done by the laser committee, and strict adherence to safety requirements by all involved staff will make the program a source of pride for the institution and ensure state-of-the-art care.